Evaluation of Tuberculosis Preventive Treatment Uptake Among People Living with HIV in PEPFAR-Supported Facilities in Zimbabwe - Timire, Collins; Mapuranga, Tawanda; Ncube, Ronald T.; Maphosa, Talent; Dube, Sithabiso; Mlilo, Nqobile; Chiteve, Cynthia; Dar Berger, Selma; Mugurungi, Owen; Kavenga, Fungai; Mutasa-Apollo, Tsitsi; Ncube, Manners; et al. (Tropical medicine and infectious disease, 2025)
Tuberculosis preventive treatment (TPT) reduces the incidence of tuberculosis (TB) among people living with HIV (PLHIV), but its coverage remains suboptimal in most settings. We conducted a cross-sectional study to describe TPT uptake among PLHIV and factors influencing TPT initiation. Healthcare workers (HCWs) in selected facilities were trained and supported to strengthen TPT management among PLHIV, including children living with HIV (CLHIV). Of 1309 enrolled PLHIV, 1268 (97%) were eligible for TPT; 1078 (85%) initiated TPT, including 663/776 (86%) among those currently on ART and 415/492 (84%) among clients newly on ART. The major reasons for not starting TPT included stock-outs of TPT medicines, TB disease, and refusal of TPT, mostly by CLHIV and adults currently on ART. Optimal and sustained uptake of TPT can be achieved through ensuring uninterrupted stocks of TPT medicines, including shorter regimens and pediatric formulations, addressing knowledge deficits among HCWs, and improving demand for TPT by educating PLHIV and caregivers of CLHIV about the benefits and risks of TPT formulations.